Preserving Ontario's Heritage: A History of the Ontario Historical Society - Killan, Gerald (My University, 1973)
This thesis seeks to relate the hitherto untold history of the Ontario Historical Society from its earliest precursors in the mid-nineteenth century to the present time. Since 1888, the OHS has been a considerable educational institution and cultural force endeavouring to develop an awareness of, and interest in, local and provincial history. Its credentials have been established by its programmes to record, interpret, publicize, and preserve Ontario's heritage, and by its efforts to co-ordinate and encourage the work of local historical associations and museums. The initial chapters provide an analysis of the nature, intent, personnel, philosophy, and accomplishments of the two lineal ancestors of the OHS -- the Historical Society of Upper Canada {est. 1861) and the United Canadian Association (est. 1872) as well as the dozen local historical groups that banded together after 1888 to create the OHS. The major emphasis of the remainder of the thesis is to illustrate how the OHS has established itself as an educational and cultural force. Its valuable role in historic preservation, a subject largely ignored by historians, is dwelt upon in detail. Another chapter provides valuable historiographical perspectives for the society's collection of publications, the largest and perhaps most important single body of material in print pertaining to the history of Ontario. The efforts of the OHS members to further the study of history in the schools and universities, to establish adequate archival and museum facilities in the province, and to assist the local historical groups, all of these are examined in each stage of the OHS's existence. So too are the motives, the philosophy, and the composition of the membership. Another major theme of this essay is that of ambition denied. For many reasons which are dealt with at length, the OHS has not been able to accomplish all of its declared objectives or to reach its full potential at any given time. Success and failure, accomplishment and frustration, go band in hand throughout its history. This work also provides valuable insights into some of the current enthusiasms of Ontarians since 1861. Nationalism and imperialism, anti-Americanists and anti-materialism, feminism and nativism, the social reform urge and the problem of assimilating new Canadians, these concerns and others are reflected in the history of the Ontario Historical Society.
Keywords: Preserving Ontario's Heritage; Ontario Historical society